Factors that influenced the acceptance of Musyarakah Mutanaqisah home financing amongst Islamic banking customer/ Wan Hasnurfishaira Wan Ismail - Wan Ismail, Wan Hasnurfishaira (Faculty of Business and Management, 2011)
Giving the better ownership of asset in home financing is a dream for everyone. The implementation of home financing under Musyarakah Mutanaqisah in Malaysia banking becomes a necessity for every bank to ensure that they are able to compete with the other home financing in the global market. As such, there are numbers of banking institution that offer Musyarakah Mutanaqisah to fulfill the needs of people even though this home financing still infant in our banking industry. In this light, with the intention of understanding and assisting the customers regarding this home financing because MM was introduced to implement the relationship of partnership in the element of sharing and. This paper aimed to investigate the factor that influenced the acceptance of Musyarakah Mutanaqisah Home Financing amongst Islamic Banking customer. Focusing on the population of 2 Islamic Banking and the sample of customer focused in Citibank Islamic in Jalan Tun Razak and RHB Islamic in Jalan Bukit Bintang at Kuala Lumpur, a total of 200 respondents have been selected to respond to the questionnaires. The investigation focused on four identifiable variables to demonstrate their influences in determining people’s acceptance towards Musyarakah Mutanqisah. The dimensions concerning attitude, subjective norm, price and promotion were selected to be the predictor of the dependent variable which influences customer’s level of acceptance. The analysis indicated that all the selected variables were significant in determining the acceptance level among people pertaining MM.